PERFORMANCE EVALUATION AND COMPARATIVE ANALYSIS OF MIRROR AUGMENTED, 2D AND 3D COMPOUND PARABOLIC CONCENTRATOR BASED PV SYSTEMS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In this present work, the performance evaluation and comparison between mirror augmented silicon PV panel system, 2D CPC based silicon PV panel system and 3D compound parabolic concentration for a simple poly-crystalline silicon solar cell of area 10 x 10 mm is examined. We compared all the three systems in view of productivity increment aspect for different inclination angles from ground horizontal surface ranging. The percentage increment in power output found in case of 3D compound parabolic concentrator is maximum of all the above mentioned systems i.e, 23% for 280. As the solar cell temperature increases, its efficiency reduces. Thus, to keep the solar cell temperature within prescribed range and also to make maximum utilization of the heat received by the sun, a thermal heat exchanger unit is installed at the back of solar panel which extracts the heat from solar cells; thereby maintaining the solar cell temperature of 250. The thermal performance in terms of efficiency achievement for utilization of heat available is evaluated for all above three systems. 3D CPC based system found the best with heat conversion efficiency ranging up to 46%.